2020
DOI: 10.1590/0037-8682-0363-2019
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of cytomegalovirus and its coinfection with Epstein-Barr virus in adult residents from Manaus: a population-based study

Abstract: Introduction: This study assessed the seroprevalence of cytomegalovirus, associated factors, and Epstein-Barr virus coinfection among adult residents of Manaus. Methods: Using a cross-sectional study design, we collected blood samples from 136 individuals in a household survey in 2016. Prevalence ratios were calculated using Poisson regression. Results: Cytomegalovirus and Epstein-Barr virus seroprevalences were 67.6% (95% CI: 9.7-75.6%) and 97.8% (95% CI: 95.3-100.0%), respectively. Coinfection was observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
(15 reference statements)
1
8
1
Order By: Relevance
“…In this study, the EBV infection and its coinfection with CMV were found to be highly prevalent among individuals of the Brazilian northern state of Amazonas who suffer from hematological diseases. The prevalence of EBV/CMV coinfection (78.51%) observed in this study was greater than the one found in the healthy adult population (66.02%) from the same region of the study population [17]. The present study suggests that patients with hematological diseases are possibly more susceptible to EBV/CMV coinfection.…”
Section: Discussioncontrasting
confidence: 59%
“…In this study, the EBV infection and its coinfection with CMV were found to be highly prevalent among individuals of the Brazilian northern state of Amazonas who suffer from hematological diseases. The prevalence of EBV/CMV coinfection (78.51%) observed in this study was greater than the one found in the healthy adult population (66.02%) from the same region of the study population [17]. The present study suggests that patients with hematological diseases are possibly more susceptible to EBV/CMV coinfection.…”
Section: Discussioncontrasting
confidence: 59%
“…Our ndings demonstrated that the CMV infection is highly prevalent among patients with hematological diseases from the Brazilian western Amazon. The study population showed a prevalence rate (91%)higher than the one observed (67.6%) in the city of Manaus [21]. Likewise, a study carried out in the Hemotherapy and Hematology Foundation of the State of Bahia (HEMOBA), in Brazil, veri ed an increased prevalence rate of CMV infection (89.4%) in patients with different hematological diseases [2].…”
Section: Discussionmentioning
confidence: 56%
“…Our findings demonstrated that the CMV infection is highly prevalent among patients from the western Brazilian Amazon with hematological diseases. The study population showed a prevalence rate (91%) that is higher than the one observed (67.6%) in the city of Manaus but, in both cases, young adults were more susceptible to CMV infection (21). Likewise, a study carried out at the Hemotherapy and Hematology Foundation in the state of Bahia (HEMOBA), in Brazil, observed an increased prevalence rate of CMV infection (89.4%) in patients with different hematological diseases (16).…”
Section: Discussionmentioning
confidence: 62%